COI gene sequence analysis for testing cyclical mating in securing genetic diversity of Macrobrachium rosenbergii. (October 2015) - Elsheikh, Mohamed Omer; Begham Mustafa, Firuza; Ibrahim Eid, Ihlam; Lutas, Ayucera; Bhassu, Subha
Abstract: In this study we analyzed sequences of the COI gene to investigate the genetic structure and diversity in four populations of the Giant Malaysian Prawn, Macrobrachium rosenbergii, and to test the effectiveness of cyclical mating as means of securing genetic diversity. Forty-three haplotypes were generated for the parental populations; most of these were unique, with moderate genetic and low nucleotide diversities. However Tajima's neutrality test indicated a significant (p < 0.05) departure of the Negeri Sembilan population from the mutation–drift equilibrium, suggesting that it may be losing genetic variability. To combat this problem we recommend a seasonal fishing ban. The AMOVA test results (5.45%, p < 0.00001), the networking of haplotypes and their phylogenetic tree all revealed clear population structuring between the populations. Genetic or haplotype diversity in the progeny groups had increased indicating that a cyclical mating system could be an effective means of maintaining it. The utilization of unique haplotypes in aquaculture, developing DNA barcodes for broods in genetic improvement programs as well as in evaluating restocking activities is recommended. For a better insight into the differences between and among the populations, further investigations using nuclear markers are required. Highlights: Mitochondrial DNA as quick marker for identification of population structure in broodstock breeding program. Method is useful for genetic and ecological studies. These biomarker have been successfully applied in cyclic mating breeding program.